Successful programming and robotics teaching experiences in basic and secondary education [Experiencias exitosas de enseñanza de programación y robótica en educación básica y media] (2019)
The accelerated evolution of technology in the world has generated great demand for professionals specialized in computer science, and particularly in programming and robotics. This implies that basic and secondary education include in the curricula and classroom plans activities for children to venture into the area in a practical, simple and contextualized manner. So, they can prepare themselves to be digital citizens and at the same time meet the society demands. This need is known by the educational institutions of the city of Medellin (Colombia), which are advancing a project whose objective is to design and evaluate a strategy of didactic-curricular intervention for training in robotics and programming from pre-garden to eleventh grade of secondary education. The first objective in the initiative is to carry out an exploration of the successful teaching strategies in the aforementioned area. Next, the results of this task are presented, showing that the teaching-learning process of robotics and programming still has aspects to improve in terms of content, infrastructure, teaching, teacher training and support tools. Some approaches are complicated and not very fun for the target audience. There are some practices that are being carried out in other countries and even schools in Medellín and Colombia and it is worth repeating them to generate motivation in the students. © 2019 AISTI.